Factors Influencing the Consumers’ Perceptions towards Frozen and Ready-to-Cook Food Products in Bangladesh - Islam, Nazrul; Tahsin, Naziah; Tarrannum, Nowshin; Salihee, Rumaisa Zahara; Sujana, Sumaiya Tarannum; Mishma, Jarin Tasneem (Nepalese Journal of Management Science and Research, 2019)
Recently in Bangladesh, frozen and ready-to-cook food industry is growing very fast due to high demand of these products by the city dwellers. This study aims at identifying the factors influencing the consumers’ perception about the frozen and ready-to-cook food products on Bangladeshi people. A survey was conducted among 211 frozen and ready-to- cook food consumers of Dhaka city with a structured questionnaire. Both descriptive and inferential statistics were used to analyze the data. Factor analysis was conducted to identify the influencing factors related to the consumers’ perception about frozen and ready-to-cook food products. Regression analysis was accomplished to examine the impact of the factors on the overall consumers’ preferences of the processed frozen and ready-to-cook food products. Results show that the factors which influence the perception of the consumers about frozen and ready-to-cook food products are concerned with saving time, helpful and economic, low price, variety and good for health, brand image and quality, availability of the frozen foods, taste of the food, and attractive packaging of the food. Individual factor relationships show that the factors such as, saving time, the foods are helpful and economic, low price, variety and good for health, brand image and quality, and availability of the foods are significant and the factors such as, good taste of the food and attractive packaging of the food are not significant in the this study. This study suggests that the policymakers of the processed frozen and ready-to-cook food product manufacturers should give importance on these factors for increasing the demand of the products among the city dwellers of Bangladesh.